Perbanyakan Tanaman Stevia (Stevia rebaudiana Bertoni) Dengan Perlakuan Stek: (Tinjauan Literatur) - Solehuddin, Darman; Tantawi, Ahmad Rafiqi (Universitas Medan Area, 2025)
Stevia (Stevia rebaudiana Bertoni) is a natural sweetener plant without calories that has great potential as a healthy sweetener alternative, especially for diabetics. Propagation of stevia through seeds has a low success rate, so the stem cuttings method is an efficient solution to maintain the superior properties of the parent plant. This study aims to review various literature on the influence of growth regulators (ZPT) on the success of stevia propagation through the stem cuttings method. The research was conducted with a descriptive-qualitative literature review approach to national and international scientific journals. The results of the study showed that the success of stevia cuttings was greatly influenced by the type of planting medium, humidity, temperature, and ZPT treatment such as IBA, NAA, or a combination in Rootone-F products. The use of mixed soil and manure media (1:1) and ZPT treatment with optimal concentrations (50–100 ppm) has been shown to improve root formation, shoots, and cutting life rates. The cuttings method is very relevant applied by Indonesian farmers because it is cheap, practical, and supports the production of superior seeds for the development of stevia agribusiness. These findings are important as the basis for planning the development of the natural sweetener industry in Indonesia in a sustainable manner.